2022
DOI: 10.3389/fcomm.2022.983929
|View full text |Cite
|
Sign up to set email alerts
|

“Listen to the science!”—The role of scientific knowledge for the Fridays for Future movement

Abstract: The Fridays for Future movement (FfF) has drawn a lot of public and academic attention in recent years. So far, studies investigated the organization, mobilization, and motives of the movement from different perspectives as well as the relevance of science for FfF. Mostly from an external point of view researchers looked at the types of science communication and its reception by the audience (i.e., framing theory). In this paper, we combine theories of science communication with the resource mobilization appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Likewise, I am worried about activists who pretend to be scientists, as this can be a misleading form of instrumentalization. In fact, there is just a thin line between the use and misuse of scientific certainty and uncertainty, and there is evidence for strategic and selective communication of scientific information for climate action 6 . (Non-)specialist activists often adopt scientific arguments as a source of moral legitimation for their movements 6 , which can be radical and destructive rather than rational and constructive.…”
Section: Climate Science and Climate Activismmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, I am worried about activists who pretend to be scientists, as this can be a misleading form of instrumentalization. In fact, there is just a thin line between the use and misuse of scientific certainty and uncertainty, and there is evidence for strategic and selective communication of scientific information for climate action 6 . (Non-)specialist activists often adopt scientific arguments as a source of moral legitimation for their movements 6 , which can be radical and destructive rather than rational and constructive.…”
Section: Climate Science and Climate Activismmentioning
confidence: 99%
“…In fact, there is just a thin line between the use and misuse of scientific certainty and uncertainty, and there is evidence for strategic and selective communication of scientific information for climate action 6 . (Non-)specialist activists often adopt scientific arguments as a source of moral legitimation for their movements 6 , which can be radical and destructive rather than rational and constructive. Unrestricted faith in scientific knowledge is, however, problematic because science is neither entitled to absolute truth nor ethical authority 7 .…”
Section: Climate Science and Climate Activismmentioning
confidence: 99%
“…They identified particular changes, including a return to more a state-centric understanding of climate politics, less focus on global climate justice frames, relatively a-political stances and a focus on science (De Moor et al, 2021;Haunss et al, 2023). So far, only few studies have focused on the understanding and integration of climate science in NCMs discourse (Buzogány and Scherhaufer, 2022;Soßdorf and Burgi, 2022;Rödder and Pavenstädt, 2023;Thierry, 2023). NCMs would tend towards strengthening the (moral) authority of science, yet they also make selective use of science, and re-frame scientific visions through simplification, dramatization, and emotional or moral appeals.…”
Section: Climate Movement Temporalities and Future Visionsmentioning
confidence: 99%
“…While in some cases activists make use of knowledge from their own research and/or that based on alternative epistemic norms [Ottinger, 2022;Rabeharisoa et al, 2014], the mobilisation of mainstream research and expertise continues to be central to much communication. Studies have indicated that activist engagement with science can be framed as 'strategic' [Soßdorf & Burgi, 2022]: while familiarity with the state of the art in relevant fields is presented as important, science may be primarily "used as a 'quiet' resource to prove that one is a serious opponent" [Fähnrich, 2018, p. 13] or is acquired in "indirect" and "idiosyncratic" ways [Unander & Sørensen, 2020]. Such work thus suggests that the epistemic practices of activists involve the assembly of relevant knowledge from various sources [Unander & Sørensen, 2020] and its use to legitimate or publicise their positions [Rohden, 2021;Soßdorf & Burgi, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that activist engagement with science can be framed as 'strategic' [Soßdorf & Burgi, 2022]: while familiarity with the state of the art in relevant fields is presented as important, science may be primarily "used as a 'quiet' resource to prove that one is a serious opponent" [Fähnrich, 2018, p. 13] or is acquired in "indirect" and "idiosyncratic" ways [Unander & Sørensen, 2020]. Such work thus suggests that the epistemic practices of activists involve the assembly of relevant knowledge from various sources [Unander & Sørensen, 2020] and its use to legitimate or publicise their positions [Rohden, 2021;Soßdorf & Burgi, 2022]. At the same time, newer protest movements (such as Fridays for Future or Extinction Rebellion) in particular often incorporate a deep respect for science, to the extent that they frame themselves as 'amplifiers' of scientific knowledge and present a 'deficit model' of existing, mainstream science communication [Rödder & Pavenstädt, 2023;Rohden, 2021].…”
Section: Introductionmentioning
confidence: 99%